Q: How do you solve 6x-2 equals x plus 13?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

5

12 + 5 equals...

To solve for x, we'd have to know what this expression equals.

Set up the equation and solve: 13 = 7 + s (next subtract 7 from each side of the equation to solve for s) 6 = s

(x - 3)(x + 5)

Related questions

5

X +13 equals 22, X equals nine

12 + 5 equals...

To solve for x, we'd have to know what this expression equals.

If: 2a+13 = 5a+1 Then: a = 4

7+6

Set up the equation and solve: 13 = 7 + s (next subtract 7 from each side of the equation to solve for s) 6 = s

6+8=14

(x - 3)(x + 5)

13=e+2 11=e (subtract 2 from each side)

6x + 8 = 13, 6x = 13 - 8, 6x = 5, x = 5/6

3h+13 = 7 3h = 7-13 3h = -6 h = -2